BETWEEN MODERNITY AND TRADITION: AFRICAN IDENTITY IN A STATE OF TRANSITION - Fouad Mami (University of Bucharest Review. Literary and Cultural Studies Series, 2011)
Tradition and modernity have been most of the time treated in scholarly debates as two diametrically-opposed apparatus of African identity. This study illustrates that contrary to this widely disseminated belief, tradition and modernity are two cronies that are simultaneously counterproductive and coercive for African communities. For, when closely examined, tradition and modernity cannot foster any viable notion of self and identity. Through our discussion of the role of tradition and the interplay of negative tradition within deplete cultures, it becomes fairly evident that the poor performance of African communities in matters related to development can be answerable when shedding light on the social context resultant from the contaminated interconnection between European modernity and African archaic traditions. The colonial legacy, the context within which European modernity and African traditions met, according to this study, should not be overlooked for any forwardlooking perspective.